2014
DOI: 10.17479/jacs.2014.4.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of In-hospital Mortality and Causes of Death in Blunt Poly-trauma Patients

Abstract: This study evaluates patterns of in-hospital mortality and causes of death in blunt poly-trauma patients. Methods: Data of blunt poly-trauma patients admitted between 2011 and 2013 were retrospectively collected and analyzed. Poly-trauma was defined as an Injury Severity Score (ISS) was greater than 15. The following variables were extracted and analyzed: age, sex, ISS, Revised Trauma Score (RTS), injury mechanism, cause of death, and patterns in-hospital mortality rate. Results: Two hundred and ten patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Trauma is a global health problem [ 1 ], causing a reported 58 million global deaths every year, which represents about 10% of all deaths [ 2 ]. Since trauma was recognized as a critical cause of death and disability in patients, multiple studies of trauma-related mortality and disability have been published [ 3 ]. According to an annual report summarizing the causes of death published by Statistics Korea, 304,948 Koreans died from trauma in 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma is a global health problem [ 1 ], causing a reported 58 million global deaths every year, which represents about 10% of all deaths [ 2 ]. Since trauma was recognized as a critical cause of death and disability in patients, multiple studies of trauma-related mortality and disability have been published [ 3 ]. According to an annual report summarizing the causes of death published by Statistics Korea, 304,948 Koreans died from trauma in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The accessibility of medical services and service quality may significantly affect an individual’s health [ 13 ]. The causes of trauma-related deaths may also vary regionally due to socioeconomic and geographical factors [ 3 , 14 ]. Many advanced nations have reported such a correlation between geographical factors and incidence of trauma [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The elderly are more susceptible to complications and death following a trauma. One study reported that a large proportion of trauma patients (21.7%) were older than 75 years [3,4]. The elderly are susceptible to more severe injuries than younger individuals, and may have a compromised physiology [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2010 [8] continued to report that brain injuries were the main cause of death, and haemorrhage as the second. However, another study [4] reported that in 2014, haemorrhage was the main cause of death following trauma, implying that active treatment of haemorrhages is key in trauma patients. The elderly are more likely to be on anticoagulant or antiplatelet medications than younger individuals, due to underlying disease [9], which increases the risk of bleeding, making initial fluid therapy and intensive monitoring even more important following an accident [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%